Locality in Humor Show entitled “Bocah Ngapa(K) Ya” - Shofi Mahmudah Budi Utami; Muammar Kadafi (Universitas Sanata Dharma, 2021)
This article discusses a humor show which was initially aired on YouTube channel entitled “Bocah Ngapa(K) Ya”. This show particularly brings out humorous content with local dialects and exhibits local nuances of the Ngapak-speaking community. This phenomenological quality expressed by the Ngapak-speaking community as ‘self’ is understood as locality through which it connects the identity of the Ngapak-speaking community with a wider audience (global society). However, the locality displayed through such kind of shows can potentially perpetuate stereotyped identity. Thus, this article examines locality displayed in a particular humor show namely “Bocah Ngapa(K) Ya” which offers an alternative identity of the Ngapak-speaking community. Central to the analysis is an argumentation that the depiction of Ngapak people in “Bocah Ngapa(K) Ya” subverts their stereotyped identity. The purpose of this study is to reveal hierarchical identities and to present an alternative to view this local identity based on the local context and humor delivery in the humor show. The method employed is cultural studies approach in order to view this cultural phenomenon. Through this study, it is found that the locality performed in this humor indicates a contemporary identity for the Ngapak people in the current era, which posits Ngapak people beyond their prevailing identity.